Organization of Halal Food in Pilgrimage Tourism - Zhobirovich, Hayitov Bekhruz (Researchparks Publishing, 2023)
The article deals with the issues of legal regulation of relations in the field of tourism activities, especially activities such as religious tourism and pilgrimage. The article substantiates the conceptual difference between these concepts, of which differences in approaches and principles for providing relevant tourism services are necessary. The significance of the impact of religious tourism on the economy of individual countries and regions of the world, religious centers. The article analyzes the conceptual regulation of tourism activities in the Republic of Uzbekistan and considers unique state programs for developing tourism and pilgrimage. And also how to organize halal food on tourist tours.